2019
DOI: 10.1002/jqs.3081
|View full text |Cite
|
Sign up to set email alerts
|

Middle Wisconsinan marine shells near Repulse Bay, Nunavut, Canada: implications for Marine Isotope Stage 3 ice‐free conditions and Laurentide Ice Sheet dynamics in north‐west Hudson Bay

Abstract: Evidence suggesting a reduction of the Laurentide Ice Sheet (LIS) during Marine Isotope Stage 3 (MIS 3) is widespread but the boundaries of the ice sheet and the timing of minimum ice extent are still poorly constrained. Radiocarbon dating of glacially transported marine mollusks in Rae Isthmus ice stream till south of Repulse Bay, Nunavut, Canada, provides new evidence for MIS 3 deglaciation in the north‐west part of Hudson Bay. Middle Wisconsinan finite 14C ages varying between 31.7 and 39.2k 14C a BP (∼35.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…1 a–c), we have set the timing of the retreat of ice from Hudson Bay in MIS 3 to coincide with Heinrich Event 5 (45,000 yr BP), with ice-free conditions only lasting a few thousand years, before becoming ice covered again by 40,000 yr BP. This timing makes it possible to explain the finite-aged radiocarbon dates found in both northern and southern Hudson Bay 5 7 . After this event, there was a gradual expansion of the ice sheet to the culmination of the LGM.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1 a–c), we have set the timing of the retreat of ice from Hudson Bay in MIS 3 to coincide with Heinrich Event 5 (45,000 yr BP), with ice-free conditions only lasting a few thousand years, before becoming ice covered again by 40,000 yr BP. This timing makes it possible to explain the finite-aged radiocarbon dates found in both northern and southern Hudson Bay 5 7 . After this event, there was a gradual expansion of the ice sheet to the culmination of the LGM.…”
Section: Resultsmentioning
confidence: 93%
“…Recent work in the Hudson Bay region in North America 5 7 shows that during part of MIS 3, ice-free conditions may have existed. Under this interpretation, the climatic conditions in this area were favorable to allow the growth of forests, with a climate that was potentially analogous to present 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence for ice-free conditions near the geographic center of the Laurentide Ice Sheet comes from radiocarbon dating of glacially transported marine mollusks in northwest J o u r n a l P r e -p r o o f Hudson Bay near Repulse Bay (Rae Isthmus ice stream; McMartin et al, 2019). In that area, eight shell samples from five sites yielded finite radiocarbon ages ranging from 35.8 ± 0.5 ka to 42.4 ± 0.5 ka (calibrated using Calib 8.1.0 and Marine 20 with 1σ error; Heaton et al, 2020;Reimer et al, 2020;Stuiver and Reimer, 1993).…”
Section: Laurentide Ice Sheetmentioning
confidence: 99%
“…Dredge and Thorleifson, 1987;Dyke et al, 2002). However, recent stratigraphic studies have reported new geochronological and biostratigraphic data from the core of glaciated regions that argue for significant changes in Northern Hemisphere ice extent during MIS 3 (Dalton et al, 2016;Helmens, 2014;McMartin et al, 2019;Sarala et al, 2016;. Furthermore, recent glacial isostatic adjustment modelling efforts support the feasibility of reduced ice cover and volume in some key areas of the formerly glaciated region (Gowan et al, 2021;Pico et al, 2018;Pico et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although documenting the growth of the Laurentide Ice Sheet is challenged by the sparsity of preserved records, recent work has refined Laurentide Ice Sheet extent and volume during MIS 3. In particular, there is an increasing number of nonglacial deposits in the Hudson Bay lowlands (Dalton et al, 2016), St. Lawrence lowlands (Parent et al, 2015), Repulse Bay (Mcmartin et al, 2019), New England (Munroe et al, 2016), and Atlantic Canada (Remillard et al, 2017), dated between 60 and 35 ka (Figure 2). This evidence suggests a substantially reduced ice sheet at ~50-35 ka relative to the LGM, with ice possibly restricted to two separate domes over eastern and western Canada at that time (Dalton et al, 2019).…”
Section: Mis 3 Laurentide Ice Sheetmentioning
confidence: 99%